On the Influence of Internal Factors on Romania’s Foreign Policy and Image - D. G. Dragan (Проблемы постсоветского пространства, 2021)
The article describes the internal processes in Romania after the collapse of the communist regime. The author attempts to determine the connection between the domestic and foreign policy of the country. This issue deserves attention since Romania's National Defence Strategy 2020–2024 prioritises the strengthening of the country's resilience and at the same time increasing international political weight. Having taken this into consideration, the author evaluates the domestic policy factors which have influenced the image of Romania in the international arena.